SIMULATION OF BINARY MIXTURES OF IDEAL BEHAVIOR IN A BATCH DISTILLATION COLUMN WITH CORRECTION - Otiniano C., Manuel (2007)
In this work it presents an procedure for to simulate the behavior of a ideal binary mixture in a batch column with rectification in the mode of operation of a constant reflux.